ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI THIN CAPITALIZATION PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - Novia Suci Nuraini; Marsono Marsono (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the factors that affect the thin capitalization of multinational companies in Indonesia. Thin capitalization is the practice of double taxation by way of finance branches or subsidiaries with greater interest debt rather than with equity. Independent variables used in this study is multinationality, utilization of tax haven, withholding taxes and institutional ownership, while the dependent variable is the thin capitalization.The population of this research is that companies listed in Indonesia Stock Exchange in 2010-2012. Sampling was done by purposive sampling technique. Based on purposive sampling, obtained a sample of 84 companies. The method of analysis used to test the effect of independent variables on the dependent variable is the Ordinary Least Square (OLS).The results of this study indicate that (1) Multinationality significant effect on thin capitalization, (2) Utilization of Tax Haven significant effect on thin capitalization, (3) Withholding Taxes significant effect on thin capitalization, and (4) Institutional Ownership significant effect on thin capitalization.